Perjanjian Investasi Bilateral: Self-Judging Sebagai Solusi? - Fakhriah, Sakina; Afriansyah, Arie (Faculty of Law, Universitas Jambi, 2022)
This article was prepared to formulate a strategy for formulating the drafting of exclusion clauses in bilateral investment treaties and legal policies that are in accordance with national security without violating international law. In its preparation, doctrinal legal research with legal objects is used which is conceptualized as a statutory rule based on the doctrine of positivism (normative juridical) schools. In the Discussion, it was found that Host Country has several options in implementing policies that put forward the national interest such as, asserting rights in agreements in good faith, including exceptions expressly, establishing definitions appropriately in agreements, mentioning special clause categories in agreements, conducting evaluations in a reasonable manner and self-judging. However, of the seven options already mentioned, self-judging is the most profitable option for host countries in implementing policies that orientate national interests. The self-judging clause is the choice of host country for two reasons. First, the clause gives the state discretion to unilaterally opt-out of international obligations and secondly, the evaluation of the elements for opt-out is not set out completely objectively from an external point of view, but only from the point of view of the state concerned.